2014
DOI: 10.1208/s12248-014-9583-x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding Assay Critical Reagents and Their Stability: Recommendations and Best Practices from the Global Bioanalysis Consortium Harmonization Team

Abstract: Abstract. The L4 Global Harmonization Team on reagents and their stability focused on the management of critical reagents for pharmacokinetic, immunogenicity, and biomarker ligand binding assays. Regulatory guidance recognizes that reagents are important for ligand binding assays but do not address numerous aspects of critical reagent life cycle management. Reagents can be obtained from external vendors or developed internally, but regardless of their source, there are numerous considerations for their reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…In this case, a correction factor based on the value of MR can be applied to the results from the new lot. The importance of the use of a correction factor when lot-dependent performance changes are observed has also been discussed elsewhere, and the reader is referred to these papers (26,27). The use of a correction factor may be considered to compensate for content and proportional errors if experimental data have been generated and are available to support.…”
Section: Solving Challenges With Lot-to-lot Differencesmentioning
confidence: 99%
“…In this case, a correction factor based on the value of MR can be applied to the results from the new lot. The importance of the use of a correction factor when lot-dependent performance changes are observed has also been discussed elsewhere, and the reader is referred to these papers (26,27). The use of a correction factor may be considered to compensate for content and proportional errors if experimental data have been generated and are available to support.…”
Section: Solving Challenges With Lot-to-lot Differencesmentioning
confidence: 99%
“…In any case, the level of criticality of reagents, their production procedure or procurement options, and any other considerations important to the assay should be documented and described in the analytical method. Since many assays are utilized over several years, the long-term availability and stability of critical reagents should be carefully considered (26).…”
Section: Validation Considerationsmentioning
confidence: 99%
“…It is advisable to monitor for trending that may indicate loss of reagent effectiveness over the duration of its use. Since many assays are utilized over a long period, stability of critical reagents should be carefully managed (26).…”
Section: Critical Assay Reagents Stabilitymentioning
confidence: 99%
“…Most importantly, with regards to our efforts, the paper acknowledged the gap in expected practices around biomarker assay calibrators, and that specific guidance around selecting and characterizing biomarker calibrator materials is needed. Thus, it was suggested that biomarker calibrators could be treated in the same way as critical reagents in the interim (16).…”
Section: Regulatory Guidance Documents and Recommendations For The Bimentioning
confidence: 99%